FLRT2 prevents endothelial cell senescence and vascular aging by regulating the ITGB4/mTORC2/p53 signaling pathway - Hwang, Hyun Jung; Kang, Donghee; Kim, Jae-Ryong; Choi, Joon Hyuk; Ryu, Ji-Kan; Herman, Allison B.; Ko, Young-Gyu; Park, Heon Joo; Gorospe, Myriam; Lee, Jae-Seon (JCI insight, 2024)
The roles of fibronectin leucine-rich transmembrane protein 2 (FLRT2) in physiological and pathological processes are not well known. Here, we identify a potentially novel function of FLRT2 in preventing endothelial cell senescence and vascular aging. We found that FLRT2 expression was lower in cultured senescent endothelial cells as well as in aged rat and human vascular tissues. FLRT2 mediated endothelial cell senescence via the mTOR complex 2, AKT, and p53 signaling pathway in human endothelial cells. We uncovered that FLRT2 directly associated with integrin subunit beta 4 (ITGB4) and thereby promoted ITGB4 phosphorylation, while inhibition of ITGB4 substantially mitigated the induction of senescence triggered by FLRT2 depletion. Importantly, FLRT2 silencing in mice promoted vascular aging, and overexpression of FLRT2 rescued a premature vascular aging phenotype. Therefore, we propose that FLRT2 could be targeted therapeutically to prevent senescence-associated vascular aging.